Squash Leaf Curl China Virus Associated with Yellow Mosaic Disease on Pumpkin in Bengkulu, Indonesia - Mimi Sutrawati; Ewa Aulia; Deri Gustian (Badan Penerbitan Fakultas Pertanian (BPFP), 2026)
Pumpkin (Cucurbita spp.) is susceptible to Begomovirus diseases, causing yellow mosaic and yield losses. This study detected and molecularly characterised a Begomovirus from yellow-mosaic-infected pumpkin in Bengkulu Utara, Bengkulu, Indonesia. Total DNA was extracted using the CTAB method and amplified using universal begomovirus primers SPG1/SPG2. PCR produced a 912 bp amplicon, confirmed by agarose gel electrophoresis. Sanger sequencing and BLASTn analysis showed the highest identity (95.20%, 99% coverage) to Squash leaf curl China Virus (SLCCV; EF197940, Malaysia). Phylogenetic analysis (MEGA X, NJ method) clustered the isolate with SLCCV from Asia (bootstrap 97%). Findings represent the first molecular confirmation of an SLCCV-related Begomovirus on pumpkin in Bengkulu, extending the known Begomovirus diversity (papaya, cucumber, weeds, eggplant) in local agroecosystems. Full genome sequencing is recommended for species demarcation.